Rainfall frequency and soil water availability regulate soil methane and nitrous oxide fluxes from a native forest exposed to elevated carbon dioxide. (29th June 2021) - Martins, Catarina S. C.; Nazaries, Loïc; Delgado‐Baquerizo, Manuel; Macdonald, Catriona A.; Anderson, Ian C.; Singh, Brajesh K.
Abstract: Free‐air carbon dioxide enrichment (FACE) experiments in terrestrial ecosystems have demonstrated ecological responses of key ecosystem processes to rising atmospheric carbon dioxide (CO2 ). However, CO2 fertilization responses in field conditions have seldom included methane (CH4 ) and nitrous oxide (N2 O), particularly in natural and mature forests, which are expected to have an important role in climate change mitigation. Herein, we aimed to capture the effect of elevated CO2 (eCO2 ; ambient vs. +150 ppm) on long‐term temporal dynamics of CH4 and N2 O fluxes, followed by identification of climo‐edaphic factors explaining feedback responses. To achieve this, continuous monitoring of greenhouse gas (GHG) fluxes using a manual chamber technique, over a 3‐year period was implemented in a mature dryland Eucalypt forest FACE (EucFACE) facility in Australia. The relationship between CH4 and N2 O fluxes with rainfall indices and soil properties was also explored since they directly impact the microbial communities in the soil responsible for CH4 and N2 O net emissions. Our results showed that in 3 years of eCO2 treatment, the amount and frequency of rainfall predicted GHG emissions in this native forest. We also found a significant reduction in CH4 sink (15%–25%) for some of the years as well as an overall treatment effect index reduction in N2 O emissions under eCO2 . Higher frequency of rain events with lower intensity led to highest CH4 sink followed by lowest N2 O emissions due to fewer wet–dry cycles. Of all the environmental variables included, soil moisture, rainfall and pH were the main predictors of net CH4 and N2 O emissions. Methane flux was also strongly influenced by soil texture. Our findings highlight the need to account for reduced forest CH4 sink under eCO2 in dryland ecosystems, which has implications for GHG budget predictions under future climate conditions. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.